Peningkatan Kemampuan Literasi melalui Model PjBL Materi Parafrase Berbasis E-Modul - Suryani, Arie; Sukestiyarno, Sukestiyarno; Syafruddin, Syafruddin (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
The aim of this research is to describe students' prose writing abilities and learning independence in paraphrasing material. The research subjects were students of class VI elementary school in the Mardisiwi cluster, Karanganyar District, Pekalongan Regency, the sampling technique used was Cluster Random Sampling. Data was collected through unstructured interviews, questionnaires, tests and documentation. Data analysis was carried out in stages, starting with quantitative analysis which included one variable t test, difference test, N-Gain test, and regression test, then continued with qualitative analysis. The results of the research show: (1) the students' ability to write prose reached a score above the specified KKM, namely 75, with a calculated t value of 2.956 (> 1.706) and a significance of 0.015 (< 0.05). (2) there was an increase in the ability to write prose by 56.72% after using the project based learning model with the help of e-modules. (3) there is an influence of student independence on prose writing ability of 93.0%, indicating that the higher the level of student independence, the better their prose writing ability.